Meridional asymmetry in the evolution of the Southern Ocean carbon sink over the 21st century in a high-resolution model - Mortenson, Eric; Lenton, Andrew; Shadwick, Elizabeth H.; Trull, Thomas W.; Chamberlain, Matthew A.; Patel, Ramkrushnbhai; Zhang, Xuebin; Wanninkhof, Rik (Frontiers in Marine Science, 2025)
The Southern Ocean plays a key role in removing anthropogenic carbon dioxide (CO2) from the atmosphere, accounting for a quarter of the global ocean uptake during the Anthropocene period. Here we show, using a high-resolution ocean model under high-emission forcing (RCP8.5), that the Southern Ocean contribution to the global ocean CO2 sink increases from 40 to 50% by 2100. This increase is accompanied by a robust poleward shift in the ocean CO2 sink. Specifically, regions north and south of the maximum zonal wind stress (located between 50-55°S) exhibit distinct carbon-uptake trajectories. The southern region (poleward of 55°S) exhibits a near-linear increase in annual carbon uptake, from near 0 to 0.75 Pg C yr-1 over the century. In contrast, the northern region (35-50°S) carbon uptake increases over the 1st half of the century, from 0.8 to 1.2 Pg C yr-1, but stagnates afterward. Our analysis indicates that the former is due to the high turnover rate (upwelling followed by subduction) of the Circumpolar Deep Water, which becomes increasingly undersaturated relative to atmospheric CO2, while the latter is due to weakening carbon solubility after the mid-21st century. Finally, the resolution in this study allows for the representation of mesoscale eddies. Eddy activity is generally enhanced along with the poleward shift in the zonal wind forcing, but its net impact on the air-sea exchange of carbon appears to be minimal.